Medically important beetles (insecta: coleoptera) of Iran - Nikbakhtzadeh,MR (2008)
This study focused on coleopteran species that are responsible for the emergence of recent cases of dermatological manifestations in Iran. To the best of our knowledge, five species of the family Meloidae and nine species of the genus Paederus are by far the only beetles recognized as medically important in Iran. The staphylinids consists of Paederus ilsae, P. iliensis, P. fuscipes, P. kalalovae, P. balcanicus, P. lenkoranus, P. littoralis, P. carpathicus, P. nigricornis, while the meloids are Mylabris impressa, M. guerini, Muzimes iranicus, Alosimus smyrnensis and Epicauta sharpi. Most cases of linear dermatitis in this country occur in areas bordering the Caspian Sea. This problem is caused by beetles of the genus Paederus which are present as adults from mid-April to October with particularly high incidences from May to August. Fars (in southern Iran) ranks second in number of cases of insect-induced dermatitis. The third major region in which this type of dermatitis has been recorded is Hamedan Province, in the west of the country. Meloid dermatitis showed its highest severity in 2001, when a considerable number of patients sought medical help in Toyserkan and Nahavand counties. New cases of skin blistering were reported along the Persian Gulf coast and the agent was identified as Epicauta sharpi (Coleoptera: Meloidae). In all these regions, it was observed that recorded cases of lesions coincided precisely with the yearly peaks of the beetles. Paederus fuscipes and P. kalalovae are the predominant species along the Caspian Sea shore. It appears that P. fuscipes is homogeneously distributed throughout the Caspian Sea region while the distribution of the other species is more irregular. Paederus fuscipes is probably the major agent that causes linear dermatitis in northern Iran. Whereas this disease is a rural difficulty in the south, mainly in villages or small towns, it is an urban problem in northern provinces along the Caspian Sea shore. Meloid dermatitis has been registered only in western and southern Iran. It is not as widespread as linear dermatitis and remains a minor rural health problem.